The impact of a reduction in fluoride concentration in the Malaysian water supply on the prevalence of fluorosis and dental caries - Mohd Nor, Nor Azlida; Chadwick, Barbara Lesley; Farnell, Damian J.J.; Chestnutt, Ivor Gordon (Wiley, 2018)
Objective: To assess the prevalence and severity of dental fluorosis and caries among Malaysian children following the reduction in fluoride concentration from 0.7 to 0.5 parts per million (ppm) in the public water supply. Methods: This study involved lifelong residents aged 9- and 12-year-olds in fluoridated and nonfluoridated areas in Malaysia (n = 1155). In the fluoridated area, children aged 12 years and 9 years were exposed to 0.7 and 0.5 ppm, respectively, at the times when maxillary central incisors developed. Standardized photographs of maxillary central incisors were blind scored for fluorosis using Dean's criteria. Dental caries was examined using ICDAS-II criteria. Results: The prevalence of fluorosis (Dean's score ≥ 2) among children in the fluoridated area (35.7%, 95% CI: 31.9%-39.6%) was significantly higher (P < 0.001) than children in the nonfluoridated area (5.5%, 95% CI: 3.6%-7.4%). Of those in the fluoridated area, the prevalence of fluorosis decreased from 38.4% (95% CI: 33.1%-44.3%) for 12-year-olds to 31.9% (95% CI: 27.6%-38.2%) for 9-year-olds, although this difference was not statistically significant (P = 0.139). The mean caries experience in the permanent dentition was significantly lower in the fluoridated area than in the nonfluoridated area for both age groups (P < 0.05). In the multivariate models, the difference in the differences of caries experience between fluoridated and nonfluoridated areas remained statistically significant. This suggests that caries-preventive effect is still maintained at 0.5 ppm. Conclusion: Findings indicate that the change in fluoride level from 0.7 to 0.5 ppm has reduced fluorosis and maintains a caries-preventive effect. Although there is a reduction in fluorosis prevalence, the difference was not statistically significant.